Relationship Between Past Food Deprivation and Current Dietary Practices and Weight Status Among Cambodian Refugee Women in Lowell, MA - Peterman, Jerusha Nelson (American Public Health Association, 2010)
Objectives. We investigated Cambodian refugee women's past food experiences and the relationship between those experiences and current food beliefs, dietary practices, and weight status. Methods. Focus group participants (n = 11) described past food experiences and current health-related food beliefs and behaviors. We randomly selected survey participants (n = 133) from a comprehensive list of Cambodian households in Lowell, Massachusetts. We collected height, weight, 24-hour dietary recall, food beliefs, past food experience, and demographic information. We constructed a measure of past food deprivation from focus group and survey responses. We analyzed data with multivariate logistic and linear regression models. Results. Participants experienced severe past food deprivation and insecurity. Those with higher past food-deprivation scores were more likely to currently report eating meat with fat (odds ratio [OR] = 1.14 for every point increase on the 9-to-27–point food-deprivation measure), and to be overweight or obese by Centers for Disease Control and Prevention (OR = 1.28) and World Health Organization (OR = 1.18) standards. Conclusions. Refugees who experienced extensive food deprivation or insecurity may be more likely to engage in unhealthful eating practices and to be overweight or obese than are those who experienced less-extreme food deprivation or insecurity.